omgineedhelp123
Junior Member
- Joined
- Nov 10, 2020
- Messages
- 87
I was taught the factoring way, so I don’t understand how to get the zeros without doing that
Sitting in the dark dank corner your eye-sight is gone. Look at the time stamp of post #4. Posted at 2:09 AM today (GMT I suppose). When did you post yours?No, no, no. I beat you to this post so you have to remove yours. Thank you.
Looks like a copy-paste of response #4 including "→". I know someone who hates those signs.h = -4.9*t^2+ 30.6*t → 0 = -4.9*t^2+ 30.6*t → t * (30.6 - 4.9 *t) = 0
There are two values of 't' that will satisfy the equation above. What are those?
Jomo gave an example. Read it carefully.Subhotosh Khan can you help?
You have factored correctlyHere is an example. If x(x-3) = 0 then with either x=0 or x-3 = 0. Well x=0 when x=0 and x-3 = 0 when x=3. So the answers are x=0 or x=3.
Jomo in his response (#16 - that I quoted) gave you an example of interpretation. Please read that carefully - then tell us what part (if any) of that response (#16) is missing you.I never learned to interpret it. My teacher just told us to factor and then find the zeros
Can you now answer my 2nd question (what are you subtracting from 30.6?)You subtract 30.6 to get 0
Alternatively:If 30.6 - 4.9 *t = 0, then 4.9t = 30.6. Then t = 30.6/4.9 = ....